Human Body Exergy Balance: Numerical Analysis of an Indoor Thermal Environment of a Passive Wooden Room in Summer - Koichi Isawa (Buildings, 2015)
To obtain a basic understanding of the resultant changes in the human body exergy balance (input, consumption, storage, and output) accompanying outdoor air temperature fluctuations, a “human body system and a built environmental system” coupled with numerical analysis was conducted. The built environmental system assumed a wooden room equipped with passive cooling strategies, such as thermal insulation and solar shading devices. It was found that in the daytime, the cool radiation exergy emitted by surrounding surfaces, such as walls increased the rate of human body exergy consumption, whereas the warm radiant exergy emitted by the surrounding surfaces at night decreased the rate of human body exergy consumption. The results suggested that the rates and proportions of the different components in the exergy balance equation (exergy input, consumption, storage, and output) vary according to the outdoor temperature and humidity conditions.